(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2012)
Financial Institutions are central to all most all Macroeconomic debates. They explain the market for money creation and Exchange the financial assets such as money stock and bonds play a central role in organizing and coordinating our economy. Financial Institutions’ position in economy is urgent position especially in the economic crises, they want to realize their profit target but this target conflicts with the target of monetary policy or fiscal policy or economic policy some time. Financial Institution assets affect in technological factors and political factor. Those factors cause increasing or decreasing in wealth of the countries. The old classical crises was form real sector to financial sector (Pushing power from real sector to financial sector). Since the modern crises is from financial sector to real sector (pushing power from financial sector to real sector) or from participant effect to real sector and financial sector. The research reached to the following major recommendations:- • It is necessary to find local and International legislation to determine the extend of financial derivatives. This step stabilizes the efficacy of financial institution in the local and international economy. • It is necessary to find a new formulation that Increases the International Financial cooperation and minimize the shocks of the International Economy which result from the fluctuations of financial institutions. • It is necessary to determine and auditing the reports of companies which are acting according to the principles of creative Accounting. • It is necessary to join and integrate under developed Economy with developed Economy to minimize the effect of crises in financial institutions.